Age and Gender Invariance in the Taiwan Wechsler Intelligence Scale for Children, Fifth Edition: Higher Order Five-Factor Model. (10th July 2020) - Chen, Hsinyi; Zhu, Jianjun; Liao, Yung-Kun; Keith, Timothy Z.
This study investigated the factorial invariance of the Taiwan Wechsler Intelligence Scale for Children, Fifth Edition (WISC-V) across age and gender. A higher order five-factor model was tested on a nationally representative sample of 1, 034 children aged 6–16 years. The results demonstrated full factorial invariance for Taiwan children of different ages and gender. The WISC-V subtests demonstrated the same underlying theoretical latent constructs, strength of relations among factors and subtests, validity of each first-order factor, and communalities, regardless of age and gender, which supported the same interpretive approach of the WISC-V. These results accord with findings in the United States, indicating a full factorial invariance of the WISC-V five-factor structure across ages and gender.